2022
DOI: 10.1177/11795514221074679
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Role for Apelin and Related Peptides in Diabetes: An Update

Abstract: Type 2 diabetes mellitus (T2DM) is an epidemic with an ever-increasing global prevalence. Current treatment strategies, although plentiful and somewhat effective, often fail to achieve desired glycaemic goals in many people, leading ultimately to disease complications. The lack of sustained efficacy of clinically-approved drugs has led to a heightened interest in the development of novel alternative efficacious antidiabetic therapies. One potential option in this regard is the peptide apelin, an adipokine that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 89 publications
(164 reference statements)
0
13
0
Order By: Relevance
“…As an adipocytokine secreted by and sensed by adipocytes, apelin is necessary for the maintenance of insulin sensitivity and tends to counteract diabetes mellitus [ 6 ]. The apelin adipocyte signaling pathway can dampen ROS generation, increase mitochondrial biogenesis, and promote the browning of WAT [ 33 ]. Furthermore, our study observed several differentially regulated EFP proteins in the AE group that can mitigate diet-induced obesity, such as the upregulated PRDX5 [ 34 ] as well as the downregulated LAMA4 [ 35 ], S27A1 [ 36 ], and HS12A [ 37 ], as reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…As an adipocytokine secreted by and sensed by adipocytes, apelin is necessary for the maintenance of insulin sensitivity and tends to counteract diabetes mellitus [ 6 ]. The apelin adipocyte signaling pathway can dampen ROS generation, increase mitochondrial biogenesis, and promote the browning of WAT [ 33 ]. Furthermore, our study observed several differentially regulated EFP proteins in the AE group that can mitigate diet-induced obesity, such as the upregulated PRDX5 [ 34 ] as well as the downregulated LAMA4 [ 35 ], S27A1 [ 36 ], and HS12A [ 37 ], as reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of clinical studies investigating apelin levels in body fluids, both in healthy controls and in patients with different pathologies, have been reported. Recent research shows that apelin peptide may be a useful adipokine in metabolic disorders and be used as a promising therapeutic target for obesity and antidiabetic drugs [4,5]. Apelin is upregulated in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that increased plasma apelin is associated with metabolic pathologies. Recent studies show that apelin peptide may be a useful adipokine in metabolic disorders and it can be a potential therapeutic target for obesity and antidiabetic drugs [4,5]. Apelin is upregulated in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous animal and clinical studies suggest that reduced levels of circulating apelin could be risk factor for HF, while an expression of its receptor was found to have been decreased in hypertrophic myocardium as well as in non-ischemic and ischemic tissues of kidneys [ 21 , 22 ]. Overall, the levels of apelin may be a promising indicator of cardiac remodeling and biomarker of effective management of HF [ 23 ]. Moreover, T2DM apelin peptides attenuated insulin resistance, improved glucose tolerance and reduced circulating fasting glucose [ 24 ].…”
Section: Introductionmentioning
confidence: 99%